Point Prevalence Study of Antibiotic Susceptibility of Genital Group B Streptococcus Isolated from Near-Term Pregnant Women in Calgary, Alberta - Deirdre Church; Julie Carson; Dan Gregson (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Genital group B streptococcus (GBS) may be transmitted from a colonized mother to her infant if appropriate intrapartum antibiotic prophylaxis is not given. A recent case of GBS neonatal sepsis occurred due to an erythromycin-intermediate strain after empirical use of this drug as intrapartum prophylaxis.